Increased Cytoplasmic CD138 Expression Is Associated with Aggressive Characteristics in Prostate Cancer and Is an Independent Predictor for Biochemical Recurrence. - Kind, Simon; Kluth, Martina; Hube-Magg, Claudia; Möller, Katharina; Makrypidi-Fraune, Georgia; Lutz, Florian; Lennartz, Maximilian; Rico, Sebastian Dwertmann; Schlomm, Thorsten; Heinzer, Hans; Höflmayer, Doris; Weidemann, Sören; et al. (BioMed Research International, 2020)
Syndecan-1 (CD138) is a transmembrane proteoglycan expressed in various normal and malignant tissues. It is of interest due to a possible prognostic effect in tumors and its role as a target for the antibody-drug conjugate indatuximab ravtansine. Here, we analyzed 17,747 prostate cancers by immunohistochemistry. Membranous and cytoplasmic CD138 staining was separately recorded. In normal prostate glands, CD138 staining was limited to basal cells. In cancers, membranous CD138 positivity was seen in 19.6% and cytoplasmic CD138 staining in 11.2% of 12,851 interpretable cases. A comparison with clinico-pathological features showed that cytoplasmic CD138 staining was more linked to unfavorable tumor features than membranous staining. Cytoplasmic CD138 immunostaining was associated with high tumor stage (p < 0.0001), high Gleason grade (p < 0.0001), nodal metastases (p < 0.0001), positive surgical margin (p < 0.0001), and biochemical recurrence (p < 0.0001). This also holds true for both V-ets avian erythroblastosis virus E26 oncogene homolog (ERG) fusion positive and ERG fusion negative tumors although the cytoplasmic CD138 expression was markedly more frequent in ERG positive than in ERG negative tumors (p < 0.0001). Comparison with 11 previously analyzed chromosomal deletions identified a conspicuous association between cytoplasmic CD138 expression and 8p deletions (p < 0.0001) suggesting a possible functional interaction of CD138 with one or several 8p genes. Multivariate analysis revealed the cytoplasmic CD138 expression as an independent prognostic parameter in all cancers and in the ERG positive subgroup. In summary, our study indicates the cytoplasmic CD138 expression as a strong and independent predictor of poor prognosis in prostate cancer. Immunohistochemical measurement of CD138 protein may thus—perhaps in combination with other parameters—become clinically useful in the future.